Cytokine Patterns in Brain Tumour Progression. (24th June 2013) - Albulescu, Radu; Codrici, Elena; Popescu, Ionela Daniela; Mihai, Simona; Necula, Laura Georgiana; Petrescu, Daniel; Teodoru, Mihaela; Tanase, Cristiana Pistol
Abstract : Inflammation represents the immune system response to external or internal aggressors such as injury or infection in certain tissues. The body's response to cancer has many parallels with inflammation and repair; the inflammatory cells and cytokines present in tumours are more likely to contribute to tumour growth, progression, and immunosuppression, rather than in building an effective antitumour defence. Using new proteomic technology, we have investigated serum profile of pro- (IL-1 β, IL-6, IL-8, IL-12, GM-CSF, and TNF- α ) and anti-inflammatory cytokines (IL-4, IL-10), along with angiogenic factors (VEGF, bFGF) in order to assess tumoural aggressiveness. Our results indicate significant dysregulation in serum levels of cytokines and angiogenic factors, with over threefold upregulation of IL-6, IL-1 β, TNF- α, and IL-10 and up to twofold upregulation of VEGF, FGF-2, IL-8, IL-2, and GM-CSF. These molecules are involved in tumour progression and aggressiveness, and are also involved in a generation of disease associated pain.